The Application of Substitute Heirs in Indonesian Islamic Inheritance Law: The Interplay of Fiqh, Customary Law, and Civil Law - Saniah, Nur; Harahap, Titi Martini (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
The implementation of the concept of substitute heirs in the Indonesian Compilation of Islamic Law (KHI) has sparked significant debate, as this concept is not found in classical fiqh texts. Article 185 of the KHI stipulates that grandchildren, whose parents have passed away, can replace their parents’ position and inherit from their grandparents. While this concept is recognized in customary law and civil law, its application in religious courts is still influenced by varying interpretations. This study aims to analyze the implementation of Article 185 of the KHI regarding substitute heirs in legal practice in Indonesia, and to explore the juridical and philosophical foundations underlying it from the perspectives of fiqh, customary law, and civil law. The research method used is a normative legal approach with doctrinal analysis, examining relevant articles in the KHI and literature related to fiqh and civil law. Additionally, the study analyzes religious court rulings related to inheritance disputes involving substitute heirs. The findings of this study indicate that, while the provision regarding substitute heirs is recognized in the KHI, its application in religious courts is often debated, primarily due to differing interpretations and the influence of local traditions. Although the concept of substitute heirs is innovative, further clarification is needed to ensure greater justice. The implications of this research suggest the need for reform in the application of inheritance law regarding substitute heirs in Indonesia, so that it better aligns with the principles of social justice, family welfare, and the social realities of Indonesian society. Furthermore, integrating fiqh, customary law, and civil law principles more effectively in religious court practices could provide better protection for the inheritance rights of children who are left without parents.